Android Smartphone Remote Monitoring Application Using SMS Service - Hadi Pranoto; Eko Budi Setiawan (IJNMT (International Journal of New Media Technology), 2017)
Android has been updating the system of every version it releases. The addition of Application Programming Interface (API) is done every time Google releases a new Android operating system. The availability of APIs for third-party applications provides opportunities for developers to be able to monitor Android smartphones. Just like Google Device Manager which can instruct Android smartphones over the internet network, however, it still has a deficiency that is if the target smartphone in a state of inactive internet. In this research, the author utilizes SMS media to be able to process instructions and access the system API for monitoring purposes. The results of this research is by using SMS then user can instruct Android smartphone to take photos, get current location, ring, delete smartphone files, set screen protection, and backup contact with higher messaging reliability. This application can run well on Android Lollipop 5.1 (API Level 22) or above because it has enough API to support system functionality.